Current IGFBP-Related Biomarker Research in Cardiovascular Disease—We Need More Structural and Functional Information in Clinical Studies - Hoeflich, Andreas; David, Robert; Hjortebjerg, Rikke (Frontiers in Endocrinology, 2018)
Cardiovascular diseases are the leading cause of death around the world and the insulin-like growth factor (IGF)-system has multiple functions for the pathological conditions of atherosclerosis. IGF binding proteins (IGFBPs) are widely investigated as biomarkers for pathological disorders, including those of the heart. At the tissue level, IGFBP-1 to -6 decrease bioactivity of IGF-I and -II due to their high affinity IGF-binding sites. By contrast, in the circulation, the IGFBPs increase biological half-life of the IGFs and may therefore be regarded as positive regulators of IGF-effects. The IGFBPs may also exert IGF-independent functions inside or outside the cell. Importantly, the circulating IGFBP-concentrations are regulated by trophic, metabolic, and reproductive hormones. In a multitude of studies of healthy subjects and patients with coronary heart diseases, various significant associations between circulating IGFBP-levels and defined parameters have been reported. However, the complex hormonal and conditional control of IGFBPs may explain the lack of clear associations between IGFBPs and parameters of cardiac failure in broader studies including larger populations. Furthermore, the IGFBPs are subject to posttranslational modifications and proteolytic degradation by proteases, upon which the IGFs are released. In this review, we emphasize that, with the exception of IGFBP-4 and in sharp contrast to the preclinical studies, virtually all clinical studies do not have structural or functional information on their biomarker. The use of analytical systems with no discriminatory potential towards intact versus fragmented IGFBPs represents a major issue in IGFBP-related biomarker research and an important focus point for the future. Overall, measurements of selected IGFBPs or more complex IGFBP-signatures of the family of IGFBPs have potential to identify pathophysiological alterations in the heart or patients with high cardiovascular risk, particularly if defined cohorts are to be assessed. However, a more thorough understanding of the dynamic IGF-IGFBP system as well as its proteases and protease inhibitors in both normal physiology and in cardiovascular diseases is necessary.